The Paleolithic imagination:Nature, science, and race in Anthropocene fitness cultures. (June 2022) - Weedon, Gavin; Patchin, Paige Marie
The widespread uptake of the Anthropocene concept over the past two decades has seen a concomitant rise in cultural forms that trade on nostalgia for Paleolithic life. Mud running, CrossFit, and the Paleo diet exemplify this trend, with the Paleolithic hunter-gatherer at the center of their popular prescriptions for healthy living. In this article, we identify these practices as embodying the anxieties of the Anthropocene as well as its historical and racial elisions. By focusing on the oblique and subtle racializations of Anthropocene health and fitness cultures, we contribute to understandings of the cultural significance of the human body in the Anthropocene and the relationship between the biopolitics of health and geological life, arguing that the body is a key site through which the tensions and inequalities of the Anthropocene are played out. And by unraveling how the Paleolithic imagination is rooted in a distinctly capitalist, Euro-American attitude to the body in nature, we show the Anthropocene to be defined by uneven distributions of health as self-optimization, and health as environmental risk. The Paleolithic imagination demonstrates the tangled politics of race, science, and nature in the twenty-first century, in which global ecological instability, the biopolitics of health, the shadows of colonialism, and consumer capitalism converge.